Variable range hopping conduction in fully dense calcium cobalt oxide textured ceramics. Issue 13 (September 2018) - Puri, Nidhi; Tandon, Ram P.; Mahapatro, Ajit K.
Abstract: Fully dense hot-pressed calcium cobalt oxide (Ca3 Co4 O9 ) pellet exhibits textures with Lotgering factor of unity and supports the ideally aligned (00 l ), l = 2, 3, 4, 5 crystallographic planes associated in the ceramics. The DC electrical conductivity of the Ca3 Co4 O9 pellets connected to metal/Ca3 Co4 O9 -pellet/metal device structures in vertical and lateral configurations follow Mott's variable range hopping. The exhibition of anisotropic ratio of 10 between the room temperature conductivity values in both the structures, reveal the presence of partially oriented textured grains in the currently developed Ca3 Co4 O9 ceramics. Graphical abstract: fx1